Wear and Friction of Polymer Fiber Composites Coated by NiCr Alloy - RAHEEM, Zainab; KAREEM, Aseel Ameer (Engineering Transactions, 2017)
The use of polymer matrix composites (PMCs) in the gas flow path of advanced turbine engines offers significant benefits for aircraft engine performance but their useful lifetime is limited by their poor environmental resistance. So the goal of this research was to develop new coatings to enhance the surface properties of PMCs In this paper, flame sprayed NiCr graded coatings are investigated as a method to address a PMC poor resistance by providing high temperature and environmental protection to PMCs. In this study, carbon fiber/epoxy composites are used as a substrate. A polyimide bond coating was prepared and deposited by a thermal evaporation technique onto the polymer composite substrate. The NiCr alloy was used as a top coating deposited by a flame spray technique. The coatings were spread with two configurations, a coating with a bond coat (with polyimide) and a coating without a bond coat (without polyimide). Wear rate measurements for both coated and uncoated samples were performed by a pin-on-disc technique. The results shows that PMCs with NiCr coatings had enhanced wear resistance as compared with the uncoated PMCs, and this was due to high hardness and wear resistance of the NiCr alloy. The wear rate increases much more with increasing temperature than it did for the coated PMCs at room temperature. The coated PMCs with bond coats (with polyimide in the bond coat) had lower friction coefficients than the coated PMCs without bond coats (without polyimide in the bond coat), and this was due to a significant increase in interface adhesion. The wear and friction resistance of all the coatings improved significantly with heat treatment. The worn surfaces and oxidation of the NiCr layer were observed by the scanning electron microscope (SEM) with X-ray diffraction (XRD).